A systematic review of the sex trafficking-related literature: Lessons for tourism and hospitality research - Wen, J.; Klarin, Anton; Goh, E.; Aston, J. (2020)
Human trafficking research has drawn increasing attention since the early 1980s. As the volume of human trafficking literature continues to expand, it is essential to examine the scope and challenges of this research area through a systematic review. Our review is based on a scientometric analysis of 2830 research articles (1982–2019) using VOSviewer. The Scopus database was utilised to retrieve bibliographic records as the core dataset to systematically review the literature on human trafficking. The overall structure of the scientometric landscape is illustrated through a three-stage process (planning/outlining a review protocol, executing the protocol, and reporting) to ensure a granular, transparent, and reliable systematic review. Our results reveal three clusters: (1) sex commercialisation, migration, and modern slavery; (2) child exploitation, sexual abuse, and health; and (3) human trafficking and institutional environments. Practical implications and future research directions are also discussed.